Pemanfaatan Media Dakwah Platform Digital di Era Generasi Z - Noviana Aini (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2023)
This study aims to analyze the strategies and challenges associated with using the digital platform for da'wah media to effectively reach Generation Z (Gen Z). The study adopts a qualitative approach and employs a literature review methodology. Primary sources used in this study include scholarly journals, books, and relevant social media platforms that cater to the interests and preferences of Gen Z. The collected data is analyzed by identifying emerging trends, strategies, and challenges in utilizing digital da'wah media for Gen Z. The findings reveal that Gen Z possesses distinctive characteristics in terms of accessing and consuming information, displaying a preference for visual, interactive, and easily accessible content through mobile devices. Consequently, an effective digital da'wah strategy for Gen Z should take these characteristics into account by focusing on content that is engaging, creative, and aligned with their interests. Challenges encountered in utilizing the digital platform for da'wah media among Gen Z include competing with entertainment content, a lack of digital literacy, and the potential dissemination of inaccurate information. This study offers recommendations for preachers and da'wah institutions in order to effectively and responsibly utilize digital platform media to reach Gen Z. These recommendations include the development of captivating and appealing content, the utilization of appropriate social media platforms, and the promotion of digital literacy among preachers.